Czy na pewno finis coronat opus? : refleksje wokół krakowskiego „Słownika historii doktryn politycznych” - Szpoper, Dariusz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The author reviews the Dictionary of the History of Political Doctrines edited by Michał Jaskólski and Krystyna Chojnicka. He notes that the dictionary is impressive in size (comprising six volumes) and content, and contributes significantly to popularizing political and legal doctrines for practical use. What is more, it supplements existing publications on the subject and serves to deepen reflection on political and legal thought. The dictionary under review is of great academic and epistemic value
Keywords: idee polityczne; historia; słowniki; państwo; prawo; recenzje